Modular Synthesis of New Pyrroloquinoline Quinone Derivatives - Janßen, Rachel; Vetsova, Violeta A.; Putz, Dominik; Mayer, Peter; Daumann, Lena J. (Synthesis, 2022)
Pyrroloquinoline quinone (PQQ) is an important cofactor of methanol dehydrogenases and glycose dehydrogenases. In addition, isolated PQQ is used as a central component in sensors and biomimetic complexes. The synthesis of PQQ derivatives is of interest for developing new alcohol oxidation catalysts and redox sensors. This work describes a modular synthesis for derivatives of PQQ bearing methyl and ketone groups instead of carboxylic acid moieties. These modifications reduce the possible coordination sites of PQQ for metal ions outside the protein environment.
Keywords: redox cofactor; pyrroloquinoline quinone; alcohol oxidation; pincer ligand; natural product derivatives